Biosensors : essentials - Evtugyn, Gennady (Berlin : Springer Verlag, 2014)
'Today, biosensors are broadly applied in research, clinical diagnosis and monitoring, as well as in pharmaceutical, environmental or food analysis. In this work, the author presents the essentials that advanced students and researchers need to know in order to make full use of this technology. This includes a description of biochemical recognition elements, such as enzymes, antibodies, aptamers or even whole cells. Various signal transducers such as electrochemical and optical transducers, luminescence devices and advanced techniques such as quartz crystal microbalances and MEMS systems are covered as well. Current applications are introduced through various case studies, rounded out by a forward-looking chapter on the prospects for biosensor development offered by nanotechnology, lab-on-a-chip, and biomimetic systems'--Page 4 of cover.
Includes bibliographical references and index.
Keywords: Biosensors